Interaksi Tektonik Konvergen Dan Pola Struktur Di Pulau Atauro, Timor-Leste - Nazario Gomes; Heru Sigit Purwanto; Sutanto Sutanto; Joko Soesilo; James Christopher (Jurnal Syntax Admiration, 2024)
This study examines convergent tectonic interactions and structural patterns on Atauro Island, Timor-Leste. Atauro Island is located near the convergence zone of the Australian and Eurasian plates within the tectonic framework of the Sunda Arc. The interaction between these plates has shaped a variety of geological features, including folded mountains, rising faults, and plateaus. In addition, these tectonic interactions are also significant in their influence on mineralization patterns on Atauro Island, involving various forms of mineralization such as precious and base metal deposits, hydrothermal systems, and related volcanic events. The research provides important insights into the tectonic history and evolution of the area. The methods used in this study involve a number of steps and approaches to collect data, analyze geological phenomena, and understand the geological processes that occur. The results, important about the types of rocks present on Atauro Island, include andesite igneous rocks and volcanic intermediate igneous rocks. Overall, this study provides a deeper understanding of the geological processes that occur on Atauro Island due to convergent tectonic interactions, as well as the potential mineral resources contained on the island.